2020
DOI: 10.1302/0301-620x.102b5.bjj-2019-1392.r2
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon proficiency in robot-assisted spine surgery

Abstract: Continuous technical improvement in spinal surgical procedures, with the aim of enhancing patient outcomes, can be assisted by the deployment of advanced technologies including navigation, intraoperative CT imaging, and surgical robots. The latest generation of robotic surgical systems allows the simultaneous application of a range of digital features that provide the surgeon with an improved view of the surgical field, often through a narrow portal. There is emerging evidence that procedure-related complicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
21
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
0
21
0
Order By: Relevance
“…In recent years, there have been many studies on the robot's advantage in accuracy and selection of pedicle screws, offering benefits for both patients and surgeons [15,[19][20][21]. Preoperative CT is used to plan screw trajectories, and intraoperative fluoroscopy is applied to register images.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, there have been many studies on the robot's advantage in accuracy and selection of pedicle screws, offering benefits for both patients and surgeons [15,[19][20][21]. Preoperative CT is used to plan screw trajectories, and intraoperative fluoroscopy is applied to register images.…”
Section: Discussionmentioning
confidence: 99%
“…10 Recent studies have demonstrated that placement of PSs with robotic assistance is controversial, with limited benefits associated with significant end-user experience variability, longer operating room times, longer training times, additional training platforms, and a long learning curve compared with traditional freehand approaches. 11,12 While some systematic reviews and trials demonstrated that other methodologies have improved outcomes when compared with robotic surgery, 13,14 there are meta-analyses that have posited the superiority of robotic approaches to PS placement. 11,15 The largest meta-analysis to date concluded that CT navigation was the optimal approach for maximizing PS placement accuracy; 16 however, it only compared single-cohort studies of indirect comparisons.…”
mentioning
confidence: 99%
“…Robotic-assisted hip arthroplasty is something that has been attempted in the past, but which must be considered afresh as new technologies have afforded an enhanced planning and user experience and will likely deliver much better results than previous iterations [ 25 ].…”
Section: Robotic Total Hip Arthroplastymentioning
confidence: 99%
“…This fits easily into the workflow of the experienced surgeon and will help with both standard and complex cases, but will also mean that there is an ideal opportunity to collect a wealth of data generated through every step of that journey from the CT all the way through planning and then changes to the plan and then final execution leading to the ultimate outcome for the patient [ 33 ]. One day soon, we will be able to use artificial intelligence and machine learning to help deliver better plans for surgeons who perhaps do a lower volume of surgery [ 25 , 34 ].…”
Section: Robotic Total Hip Arthroplastymentioning
confidence: 99%